Psychosocial Risk Profiles Among American and Dutch Families Affected by Pediatric Cancer. (20th March 2020) - Sharkey, Christina M; Schepers, Sasja A; Drake, Sarah; Pai, Ahna L H; Mullins, Larry L; Grootenhuis, Martha A
Abstract: Objective: Little is known about relations between domains of psychosocial risk among pediatric cancer populations. The Psychosocial Assessment Tool 2.0 (PAT2.0) is one internationally validated screening measure that can examine these relations. This study aimed to examine risk profiles and predictors of these patterns exhibited by American and Dutch families. Methods: Caregivers of children newly diagnosed with cancer ( N = 262; n USA =145, n NL =117) completed the PAT2.0 as part of larger studies conducted in the United States and the Netherlands. Latent profile analysis and multinomial logistic regression examined differences in demographic and medical variables across risk profiles. Domains assessed included Family Structure/Resources, Child Problems, Sibling Problems, Family Problems, Caregiver Stress Reactions, and Family Beliefs. Results: Four groups were identified: "Low-Risk" ( n = 162) defined by generally low risk across domains; "Moderate-Caregiver" ( n = 55) defined by elevated Caregiver Stress Reactions domain; "Moderate-Children" ( n = 25) defined by elevated Child Problems and/or Sibling Problems, and "Elevated-Risk" ( n = 20) marked by generally high overall risk. Dutch families had higher odds of being in the Elevated-Risk group, compared to the Low-Risk group. Caregiver age, gender, and educational attainment predicted group membership. Families classified as Targeted or Clinical had higher odds of being in the Moderate or Elevated risk groups. Conclusion: The PAT2.0 appears to identify largely similar patterns of risk, suggesting that families experience common psychosocial difficulties in both American and Dutch societies. The two Moderate groups demonstrated specific risk sources, suggesting that evaluation of domain patterns, rather than reliance on PAT2.0 risk level, could be of clinical benefit.